Penerapan Intrusion Detection dan Prevention System untuk Mendeteksi Serangan Metasploit Menggunakan Snort dan Wireshark - Sirait, Asri yohana; Silalahi, Rivka Salvita; Naibaho, Samuel Volder (JURNAL QUANCOM: QUANTUM COMPUTER JURNAL, 2025)
Network security is crucial as cyberattacks continue to rise. One common type of attack is a Remote Exploit, which exploits vulnerabilities in insecure protocols or open ports to remotely access a computer's operating system and steal data. A popular tool used for such attacks is the Metasploit Framework, which is widely used for network security testing. Metasploit includes a module called exploit/multi/handler, which facilitates receiving connections from a target after a security vulnerability is successfully exploited. Additionally, payloads such as linux/x64/meterpreter/reverse_tcp are often utilized to gain control of the target device. Meterpreter is a sophisticated payload that enables attackers to execute commands, extract data, or install malicious programs on the target computer. The reverse_tcp feature ensures the victim's computer establishes a connection back to the attacker, making access easier and less detectable. To protect networks against such threats, tools like Security Information and Event Management (SIEM) systems can be combined with Intrusion Detection Systems (IDS) such as Snort. IDS tools monitor network traffic, detect suspicious activities, and issue alerts when threats are identified. Additionally, tools like Wireshark can be used for analyzing network data, while VirusTotal helps check whether detected files or data contain viruses. By combining these tools, network security can be enhanced to better combat increasingly sophisticated threats.